Process Evaluation of Facility Delivery Services in Northwest Ethiopia: In the Case of Public Health Centers - Tafere TZ; Aschalew AY; Tsehay CT; Gebremedhin T (Dove Medical Press, 2023)
Tesfahun Zemene Tafere, Andualem Yalew Aschalew, Chalie Tadie Tsehay, Tsegaye Gebremedhin Department of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Tesfahun Zemene Tafere, Department of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, P.O. Box: 196, Gondar, Ethiopia, Email tesfahunzemene4@gmail.comBackground: Even if giving birth at health facility is vital for both the mothers and their newborns, the coverage of institutional delivery in Ethiopia is very low (50%). In that regard, several studies have shown the possible factors of low delivery service uptake from the patients' side, but evidences on delivery services at the health centers are meagre. This study aimed to evaluate the process of delivery services in public health centers of northwest Ethiopia.Methods: A case study evaluation design with an embedded mixed-method was used to evaluate institutional delivery in public health centers of Gondar city. Dimensions from the access (availability, accommodation, and acceptability) and implementation fidelity (compliance) frameworks were used. A total of 363 mothers, 32 document reviews, 32 direct observations, and 17 key informants were included. The qualitative data were transcribed, translated, coded, and analysed using a thematic analysis approach. The overall process of institutional delivery services was measured based on pre-determined judgmental criteria.Results: The overall facility delivery process was 75.1%, judged by availability (78.5%), compliance (70.6%), accommodation (68.8%), and acceptability (80.2%) of services. Essential medicines in some of the health centers were stockout, insufficient delivery rooms and inadequate training of health workers on obstetric and newborn care were observed. Using partograph and examining vulval-perineal region for possible laceration during intrapartum period were less practiced. Residence (AOR: 0.13, 95% CI: 0.06- 0.30), ANC 1 to 3 visits (AOR: 2.65, 95% CI: 1.05- 6.74) and ANC4+ (AOR: 5.57, 95% CI: 2.09, 14.84) were factors affected acceptability of delivery services.Conclusion: Major constraints were in the accommodation of delivery services which needs a holistic effort from all stakeholders. Therefore, implementors with other stakeholders shall improve delivery rooms, facilitate training, and provide parenteral drugs as part of the obstetric and newborn care to improve the facility delivery services in Ethiopia.Keywords: acceptability, accommodation, availability, compliance, institutional delivery, evaluation